Cardiovascular outcomes among HIV-infected veterans receiving atazanavir. (24th September 2017) - LaFleur, Joanne; Bress, Adam P.; Rosenblatt, Lisa; Crook, Jacob; Sax, Paul E.; Myers, Joel; Ritchings, Corey
Abstract : Objective: Patients with HIV infection have an increased risk of cardiovascular disease compared with uninfected individuals. Antiretroviral therapy with atazanavir (ATV) delays progression of atherosclerosis markers; whether this reduces cardiovascular disease event risk compared with other antiretroviral regimens is currently unknown. Design: Population-based, noninterventional, historical cohort study conducted from 1 July 2003 through 31 December 2015. Setting: Veterans Health Administration hospitals and clinics throughout the United States. Participants: Treatment-naive patients with HIV infection ( N = 9500). Antiretroviral exposures: Initiating antiretroviral regimens containing ATV, other protease inhibitors, nonnucleoside reverse transcriptase inhibitors (NNRTIs), or integrase strand transfer inhibitors (INSTIs). Main outcome/effect size measures: Incidence rates of myocardial infarction (MI), stroke, and all-cause mortality within each regimen. ATV versus other protease inhibitor, NNRTI, or INSTI covariate-adjusted hazard ratios by using Cox proportional hazards models and inverse probability of treatment weighting. Results: Incidence rates for MI, stroke, and all-cause mortality with ATV-containing regimens (5.2, 10.4, and 16.0 per 1000 patient-years, respectively) were lower than with regimens containing other protease inhibitors (10.2, 21.9, and 23.3 per 1000 patient-years), NNRTIs (7.5, 15.9, and 17.5 per 1000 patient-years), or INSTIs (13.0, 33.1, and 21.5 per 1000 patient-years). After inverse probability of treatment weighting, adjusted hazard ratios (95% confidence intervals) for MI, stroke, and all-cause mortality with ATV-containing regimens versus all non-ATV-containing regimens were 0.59 (0.41–0.84), 0.64 (0.50–0.81), and 0.90 (0.73–1.11), respectively. Conclusion: Among treatment-naive HIV-infected patients in the Veterans Health Administration initiating ATV-containing regimens, risk of both MI and stroke were significantly lower than in those initiating regimens containing other protease inhibitors, NNRTIs, or INSTIs. Abstract : Supplemental Digital Content is available in the text